Age-associated decline of monocyte insulin sensitivity in diabetic and healthy individuals. (February 2021) - Nakamura, Suguru; Mori, Kentaro; Okuma, Hideyuki; Sekine, Tetsuo; Miyazaki, Asako; Tsuchiya, Kyoichiro
Objective: It is unclear whether monocyte/macrophage insulin signaling in humans is affected by type 2 diabetes (T2DM), systemic insulin sensitivity, and other unknown factors. Research design and methods: Fifty-three adult volunteers (control group) not taking any medication and without cardiovascular risk factors, and 59 patients with T2DM (T2DM group) were included. Monocytes were isolated and cultured from all participants. Results: In cultured monocytes, insulin-stimulated AKT and FOXO3 phosphorylation was significantly suppressed in T2DM compared with that in the control group. Insulin-stimulated phosphorylation of AKT was significantly correlated with body mass index and serum insulin level only in the control group. In both groups, significant negative correlation between age and insulin-stimulated phosphorylation of AKT and FOXO3 was commonly observed. In the control group, lipopolysaccharide (LPS)-stimulated induction of TNFA, and NOS2 was significantly and negatively correlated with insulin-stimulated AKT phosphorylation. Age was also significantly correlated with LPS-stimulated induction of TNFA . Discussion: Aging plays an important role in the development of monocyte insulin resistance, not only in patients with T2DM but also in healthy participants. Monocyte insulin sensitivity is negatively correlated with inflammatory responses and may be helpful for subclinical risk assessment of CVDs and/or insulin resistance in participants without risk factors.